The potential of waste cooking oil as bio-asphalt for alternative binder – An overview - Wan Azahar, Wan Nur Aifa; Bujang, Mastura; Putrajaya, Ramadhansyah; Hainin, Mohd Rosli; Mohamed, Azman; Ngadi, Norzita; Jayanti, Dewi Sri (UTM Press, 2016)
Enormous quantity of waste products from by-products of frying activity could cause negative impact if not properly managed and disposed. Therefore, recyclability of Waste Cooking Oil (WCO) in binder modification to produce bio-asphalt can be a sustainable ways to minimize waste dumping while at the same time to reduce the usage of natural resources. Bio-asphalt can be described as alternative asphalt binder which differs from conventional asphalt in terms of strength and durability. This review has highlighted the potential of bio-binder to replace with conventional binder by the addition of waste cooking oil in the mixture.